Analysis of lightning events due to rainfall and wind speed in Pekanbaru City - Defrianto Defrianto; Lihayardi Lihayardi; Usman Malik (Science, Technology, and Communication Journal, 2022)
Quantitative research has been conducted on the effect of rainfall and wind speed on lightning events in Pekanbaru City from August to October 2018. Observation data were obtained from Meteorological Station Class I Sultan Syarif Kasim II Pekanbaru, Riau Province, Indonesia. Observations are made by recording lightning events automatically using a lightning detector which will be analyzed using the Lightning Analysis program version 7.2 and the Google Earth Pro program. The results showed that high rainfall caused frequent thunderstorms, and relatively high wind speeds from late September to October caused the number of lightning strikes to increase due to the ionization process that produces an electric charge.